2002
DOI: 10.1136/aim.20.2-3.56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture on Intraoperative and Postoperative Analgesic Requirement

Abstract: Acupuncture has been shown to be effective in experimental and clinical acute pain settings. This study aims to evaluate the effect of preoperative electroacupuncture (EA) on intraoperative and postoperative analgesic (alfentanil and morphine) requirement in patients scheduled for gynaecologic lower abdominal surgery. Ninety patients were randomly assigned to one of three groups: Group I (control group) –received placebo EA for 45 minutes before induction of general anaesthesia (GA); Group II –preoperative EA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 28 publications
(28 reference statements)
0
83
1
3
Order By: Relevance
“…15 Beyond this, the effectiveness of preincisional electroacupuncture in reducing opioid requirements has been shown. 16,17 On the one hand, preincicsional TENS might produce differential effects on the production of pain-producing substances (eg, substance P, potassium, hydrogen ions, lactic acid, and bradykinin) immediately before skin incision. On the other hand, preincisional TENS influences the conductance of painful stimuli via k-receptors by producing ir-dynorphin A.…”
Section: Discussionmentioning
confidence: 99%
“…15 Beyond this, the effectiveness of preincisional electroacupuncture in reducing opioid requirements has been shown. 16,17 On the one hand, preincicsional TENS might produce differential effects on the production of pain-producing substances (eg, substance P, potassium, hydrogen ions, lactic acid, and bradykinin) immediately before skin incision. On the other hand, preincisional TENS influences the conductance of painful stimuli via k-receptors by producing ir-dynorphin A.…”
Section: Discussionmentioning
confidence: 99%
“…The use of EA in the preoperative of gynaecological surgery permitted the reduction in the consumption of opioids during and after surgery. 12 However, the use of preoperative EA is not a common practice as EA sessions are usually conducted immediately before surgery. That fact reduces its practical application because of other intensive demands of the surgical centre at that critical time and acupuncturists' reality (most acupuncturists do not work at hospitals and very few hospitals have a structured acupuncture department), which hinders the use of this technique immediately before surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that patients receiving electrical stimulation applied at the traditional Chinese acupoints (electroacupuncture) prior to surgery have a lower level of pain, reduced opioid requirement, a lower incidence of post-nausea and vomiting, and lower sympatho-adrenal responses [2][3][4][5][6] . In addition, other studies have demonstrated that the electrical stimulation applied at the dermatomal levels corresponding to the skin incision also reduces pain and postoperative opioide analgesic requirement 7,8 .…”
Section: Introductionmentioning
confidence: 99%